Left atrial remodelling after septal myectomy is associated with a reduced 5-year risk of atrial fibrillation in hypertrophic cardiomyopathy. (3rd October 2022) - Bataiosu, R; Scolari, F L; Brahmbhatt, D; Hoss, S; Chow, C; Cooper, C; Tsoi, M; Rowin, E; Maron, M S; Billia, F; Ralph-Edwards, A; Rakowski, H; et al.
Abstract: Background: Left atrial diameter (LAD) is an established predictor of atrial fibrillation (AF) and adverse outcomes in hypertrophic cardiomyopathy (HCM). However, the impact of LAD remodelling after surgical myectomy on the development of late onset AF is still poorly understood. Purpose: To investigate the association between LAD remodelling and new occurrence of AF in the first five years after surgical myectomy in a large patient population with HCM. Methods: 1177 HCM patients without a history of AF, subjected to surgical myectomy at two referral centres between 2001 and 2020 were retrospectively reviewed. Paired echocardiographic studies before and shortly after surgical myectomy were available in 894 (76%) patients and 889 (75%) patients had complete LAD measurements, defined as the anteroposterior diameter at end-systole from parasternal long axis view. LAD was considered normal when ≤40mm. Late onset AF was determined as AF documented between one month and 5 years follow up after myectomy. Patients were grouped as having normal LAD pre- and post-myectomy (group 1), enlarged pre-myectomy LAD but normal post-myectomy LAD (group 2), and those with enlarged LAD post-myectomy (group 3). Cox proportional hazards models were applied to evaluate the impact of LAD on late onset AF. Results: Late onset AF was detected in 63 (7%) patients, 56% male, with an incidence of 1%/year. Patients with AF were older (56±13 vs. 52±14 years, p=0.03), had a larger post-surgery LAD (44±7 vs. 41±6 mm, p<0.001) and a lower left ventricular ejection fraction (58±6 vs. 61±6%, p=0.002) compared to patients without AF. Postoperative left ventricular maximal wall thickness (14±4 mm vs. 15±4mm, p=0.53), left ventricular outflow tract obstruction (6% vs. 8%, p=0.49) or moderate/severe mitral regurgitation (13% vs. 9%, p=0.29) were similar between patients with and without late onset AF. Among the 227 patients in group 1, late onset AF occurred in only 5 (3%), in comparison to 8 (5%) of 182 patients in group 2, and in 36 (10%) of the 480 patients in group 3 (p=0.006). Using group 1 as reference, the hazard ratio for developing AF was 2.1 (95% CI 0.7–6.5, p=0.15) for patients in group 2 and 3.5 (95% CI 1.4–9.4, p=0.005) for patients in group 3. Conclusion: In our study we were able to show that the overall post-myectomy 5-year risk for developing AF was 1%/year. Normal LAD and reverse LAD remodelling correlated with a lower risk for developing late onset AF, whereas a higher risk was associated with enlarged post-myectomy LAD. These results highlight the possible clinical benefit of LAD remodelling after myectomy in reducing late onset AF. Funding Acknowledgement: Type of funding sources: None.